2020
DOI: 10.1177/1078155220908924
|View full text |Cite
|
Sign up to set email alerts
|

Describing the role of the hematology/oncology clinical pharmacist in health information technology

Abstract: Purpose To describe the role of hematology/oncology clinical pharmacists in health information technology as well as their perceptions of the impact of technology expansion on patient care. Methods A single-center, web-based survey was distributed to 30 hematology/oncology clinical pharmacists by email over the two-week-period of 24 September 2018 to 8 October 2018. The anonymous survey was composed of 19 questions, with varying formats including multiple choice, fill-in-the-blank, and rank order. Primary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The oncology pharmacist plays an essential role in the treatment of clinically complex patients. 7,8 The main contributions of clinical pharmacists in assisting onco-hematological patients include: evaluating the medical prescription regarding quantity, quality, compatibility, stability and interactions; supportive care management, such as managing anti-infectious therapies; assistance in the transition of care; evaluation of patients regarding the toxicity of chemotherapies and treatment effectiveness, in addition to tracking iatrogenic effects; educating patients, caregivers, as well as health professionals and interns; monitor, evaluate and report results related to treatment to help improve clinical practice. 913 Such activities are essential to promote patient safety when using antineoplastic agents and to avoid unnecessary expenses with the use of ineffective drugs for the patient or hospitalizations caused by complications resulting from medication errors that could be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…The oncology pharmacist plays an essential role in the treatment of clinically complex patients. 7,8 The main contributions of clinical pharmacists in assisting onco-hematological patients include: evaluating the medical prescription regarding quantity, quality, compatibility, stability and interactions; supportive care management, such as managing anti-infectious therapies; assistance in the transition of care; evaluation of patients regarding the toxicity of chemotherapies and treatment effectiveness, in addition to tracking iatrogenic effects; educating patients, caregivers, as well as health professionals and interns; monitor, evaluate and report results related to treatment to help improve clinical practice. 913 Such activities are essential to promote patient safety when using antineoplastic agents and to avoid unnecessary expenses with the use of ineffective drugs for the patient or hospitalizations caused by complications resulting from medication errors that could be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the study showed pharmacists felt patient care is safer, of better quality, and more efficient with the advance of EHR technology. 19 However, EHRs present challenges for consistent data extraction due to their often unstructured and incomplete nature. 20,21 This emphasizes the need for more robust EHR design and the integration of EHR with claims data.…”
Section: Discussionmentioning
confidence: 99%